Progesterone and RU486: opposing effects on human sperm. - Yang, J (1994)
Progesterone induced a rapid influx of calcium in capacitated human sperm, followed by a long-lasting, dose-dependent increase of intracellular free calcium. Thereafter, progesterone increased the fraction of hyperactivated sperm and the acrosome reaction. On the contrary, the progesterone antagonist RU486 (mifepristone) induced an immediate and transient, dose-dependent decrease of intracellular free calcium and a drop in the values of sperm movement parameters related to hyperactivation. Moreover, RU486 counteracted the effects of progesterone on calcium influx, lateral sperm head displacement, and the acrosome reaction. Therefore, RU486 effects were opposite to those of progesterone. The nature of the membrane receptor(s) involved is unknown. Several steroids bearing 11 beta-phenyl substitutions, with different pharmacological profiles, were also investigated. It was concluded that the steroid structure and chemical groups added to the 11 beta-phenyl influence effects on calcium influx.